Incidence of thymic tissue in pediatric thyroidectomy. (July 2022) - Sahyouni, Grace; Osterbauer, Beth; Park, Soyun; Paik, Connie; Austin, Juliana; Kwon, Daniel; Gomez, Gabriel
Abstract: Objectives: The nuances in the technical approach to pediatric thyroidectomy have been sparsely reported in the literature. No previous studies have reported on the rates of unintentional thymic tissue excision during pediatric thyroidectomy. In this study, we sought to describe the rates of thymic tissue excision noted on surgical specimens from pediatric thyroidectomies and investigate any correlations with preoperative factors and long-term outcomes. Methods: A retrospective chart review was conducted of patients who underwent thyroidectomy at a tertiary care children's hospital between January 2010 and October 2020. Presence of thymic tissue (PTT) was defined as any pathologist-documented evidence of thymic tissue in the surgical specimen. Patient characteristics, operative details, and disease related datapoints were investigated for any correlation with PTT. Results: Of the 209 patients who underwent thyroidectomy in the study period, 53 (25%) had PTT. After conducting a stepwise multivariate analysis, those with a concomitant central neck dissection had 3.3 times the odds of having PTT as compared to those with no neck dissection (p = 0.013, 95%CI: 1.3, 8.3). Additionally, patients with evidence of incidental parathyroidectomy had 8.99 times the odds of also having PTT as compared to those without IPE (p < 0.001, 95%CI: 4.0, 20.1). Conclusion: This is the first report analyzing the rate of thymic tissue excision during pediatric thyroidectomy. Thyroid surgeons should be prepared to encounter thymic tissue during pediatric cases and be aware of its associated risk of incidental parathyroid gland excision and dissection of tissue beyond intended surgical limits. Highlights: Hypoparathyroidism occurs commonly following thyroidectomy in children. Dissection into thymic tissue may contribute to post-operative hypoparathyroidism. This is the first report of thymic tissue excision with pediatric thyroidectomy. Thymic tissue excision has risk of incidental parathyroid gland excision.